(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
In high-tech & inventive companies, innovation & technology management is an unavoidable problem. Organizations must always concentrate on new product creation in order to maintain market leadership. Innovations play a critical part in product development in any company in order to expand business quicker, improve efficiency, & assist any organization dominate in global market. In present scenario, every company is attempting to integrate technology in workplace in order to provide a better route to innovation that will enable them to outperform ir rivals. Any organization’s business is immediately affected by technological innovation, which is why good management of innovation & technology is critical inside company. Effective management may assist any company in maintaining its market leadership position. This article offers an overview of business innovation, concentrating on various kinds of innovation depending upon several criteria, technological innovation in digital business environment, obstacles, & technological innovation management.